2013
DOI: 10.1103/physrevb.88.094406
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulations of the fcc kagome lattice: Competition between triangular frustration and cubic anisotropy

Abstract: The impact of local cubic anisotropy on the magnetic states of the Heisenberg model on the fcc kagome lattice are examined through classical Monte Carlo simulations. Previous simulations revealed that the macroscopic degeneracy of the two-dimensional (2D) kagome exchange-coupled co-planar spin system partially persists in the 3D case of ABC stacked layers giving rise to a discontinuous phase transition. Local cubic anisotropy is shown to remove this degeneracy by re-orienting the spins out of the co-planar con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 21 publications
(31 reference statements)
4
25
0
Order By: Relevance
“…The most popular compound for use as the antiferromagnet in spin valves for magnetic recording is IrMn 3 , which in its ordered crystalline fcc phase is composed of ABC stacked [111] planes of magnetic Mn ions on kagome sites. 4,5,[11][12][13][14][15] The large number of studies over the past few decades on the near-neighbor antiferromagnetic exchange Heisenberg kagome model have shown that the large degeneracy associated with the 120…”
Section: 8mentioning
confidence: 99%
“…The most popular compound for use as the antiferromagnet in spin valves for magnetic recording is IrMn 3 , which in its ordered crystalline fcc phase is composed of ABC stacked [111] planes of magnetic Mn ions on kagome sites. 4,5,[11][12][13][14][15] The large number of studies over the past few decades on the near-neighbor antiferromagnetic exchange Heisenberg kagome model have shown that the large degeneracy associated with the 120…”
Section: 8mentioning
confidence: 99%
“…Anisotropy serves to lift the spin vectors out of the plane and induce a finite magnetization in a 111 direction. 13 This effect is characterized by α, the cosine of the angle between each sublattice spin and its anisotropy axis (α = cos(S i • n i ), i = A, B, C), and β, the cosine of the angle with respect to the other two anisotropy axes (β = cos(S i • n j ), i = j) where α 2 + 2β 2 = 1. The modified ground state energy per spin that includes further-neighbor exchange is given by (compare Eqs.…”
Section: Model Resultsmentioning
confidence: 99%
“…Note that there are eight degenerate ground states corresponding to the eight 111 axes. 13 The analysis of spin excitations in this section correspond to a single domain [111] crystal. Powder averaged results are discussed in the following section.…”
Section: Model Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the flat band is a direct consequence of the absence of interlayer couplings within our model. If we consider interlayer exchange interaction including the terms outside the plane (111) in the gradient expansion, the flat band is modified as is shown in 14,21 . …”
Section: Spin Wave Spectramentioning
confidence: 99%